2007
DOI: 10.1080/14786410601083845
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure determination of a lignan from the bark ofSalix alba

Abstract: A lignan, sisymbrifolin (1) found in the fruits of Solanum sisymbriflolium has been isolated from the bark extract of Salix alba (Salicaceae). Its structure was elucidated by its direct spectrum data of ESI-MS and one- and two-dimensional NMR spectroscopy for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The 13 C-NMR spectrum ( Table 1 ), coupled with HSQC analysis, exhibited the signals of twenty-two carbons in total, comprising three methyls, two oxymethylenes [δ C 64.3 (C-9′) and 66.7 (C-9)], nine methines (including five aromatic methanes), and eight quaternary carbons [including a carboxyl group at δ C 172.7 and seven aromatic quaternary carbons]. Detailed analysis of the NMR data indicated that compound 2 closely resembled threo -dihydroxydehydrodiconiferyl alcohol [ 20 , 21 , 22 ], with the only difference of the hydroxyl group at C-9 being replaced by an acetoxy group in 2 . This deduction was consistent with the molecular formula and in accord with the significant HMBC correlations ( Figure 2 ) from δ H 4.33 and 4.44 (C-9) to δ C 172.7.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C-NMR spectrum ( Table 1 ), coupled with HSQC analysis, exhibited the signals of twenty-two carbons in total, comprising three methyls, two oxymethylenes [δ C 64.3 (C-9′) and 66.7 (C-9)], nine methines (including five aromatic methanes), and eight quaternary carbons [including a carboxyl group at δ C 172.7 and seven aromatic quaternary carbons]. Detailed analysis of the NMR data indicated that compound 2 closely resembled threo -dihydroxydehydrodiconiferyl alcohol [ 20 , 21 , 22 ], with the only difference of the hydroxyl group at C-9 being replaced by an acetoxy group in 2 . This deduction was consistent with the molecular formula and in accord with the significant HMBC correlations ( Figure 2 ) from δ H 4.33 and 4.44 (C-9) to δ C 172.7.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics for the study of willow is still in its infancy with a handful of studies focusing on the phytochemical properties of willow bark and leaves (Du et al, 2007 ; Förster et al, 2010 ; Agnolet et al, 2012 ), the inhibitory compounds in lignocellulosic willow wood chips hydrolysates (Zha et al, 2014 ), and the chemical composition of the cuticular wax in relation to biomass productivity (Teece et al, 2008 ). These studies report on the accumulation of primary and secondary metabolites in the aerial parts of AMF willows.…”
Section: Introductionmentioning
confidence: 99%
“…Salix species have been used to treat pain, inflammation, and fever since ancient times (Du et al, 2007;Freischmidt et al, 2012). Moreover, Salix species also have anti-oxidant (Alam et al, 2006), anti-inflammatory (Li et al, 2008), antiobesity (Han et al, 2003), and anti-tumor (Sultana et al, 2004) effects.…”
Section: Introductionmentioning
confidence: 99%